Role of Stalking in Domestic Violence Crime Reports Generated by the Colorado Springs Police Department, 1998 - Tjaden, Patricia ([Verlag nicht ermittelbar], 2001)
This study examined the role of stalking in domestic violence crime reports produced by the Colorado Springs Police Department (CSPD). It provided needed empirical data on the prevalence of stalking in domestic violence crime reports, risk factors associated with intimate partner stalking, and police responses to reports of intimate partner stalking. The study was conducted jointly by the Justice Studies Center (JSC) at the University of Colorado at Colorado Springs and the Denver-based Center for Policy Research (CPR). JSC staff generated the sample and collected the data, and CPR staff processed and analyzed the data. The sample was generated from CSPD Domestic Violence Summons and Complaint (DVSC) forms, which were used by CSPD officers to investigate crime reports of victims and suspects who were or had been in an intimate relationship and where there was probable cause to believe a crime was committed. During January to September 1999, JSC staff reviewed and entered information from all 1998 DVSC forms into a computerized database as part of the evaluation process for Domestic Violence Enhanced Response Team (DVERT), a nationally recognized domestic violence prevention program. A subfile of reports initiated during April to September 1998 was generated from this database and formed the basis for the study sample. The DVSC forms contained detailed information about the violation including victim and suspect relationship, type of violation committed, and specific criminal charges made by the police officer. The DVSC forms also contained written narratives by both the victim and the investigating officer, which provided detailed information about the events precipitating the report, including whether the suspect stalked the victim. The researchers classified a domestic violence crime report as having stalking allegations if the victim and/or police narrative specifically stated that the victim was stalked by the suspect, or if the victim and/or police narrative mentioned that the suspect engaged in stalking-like behaviors (e.g., repeated following, face-to-face confrontations, or unwanted communications by phone, page, letter, fax, or e-mail). Demographic variables include victim-suspect relationship, and age, race, sex, and employment status of the victim and suspect. Variables describing the violation include type of violation committed, specific criminal charges made by the police officer, whether the alleged violation constituted a misdemeanor or a felony crime, whether a suspect was arrested, whether the victim sustained injuries, whether the victim received medical attention, whether the suspect used a firearm or other type of weapon, whether items were placed in evidence, whether the victim or suspect was using drugs and/or alcohol at the time of the incident, number and ages of children in the household, whether children were in the home at the time of the incident, and whether there was a no-contact or restraining order in effect against the suspect at the time of the incident.